'And Everybody Did Whatever They Wanted to Do': Informal Practices of International Statebuilders in Kosovo. Issue 2 (3rd April 2018) - Distler, Werner
ABSTRACT: Informal practices of local actors in Kosovo have been harshly criticised by international statebuilding actors. However, it would be short sighted to ignore the role of informal practices of international actors in the post-conflict political economy. Working with a qualitative political economy framework, which focuses on the emergence of the socioeconomic post-war order, I argue that we can observe a range of impactful informal practices of international actors in key socio-economic fields. Instead of solely focusing on local informality, we have to trace informal practices of international actors and assess their role in the formation of peace economies.